Kemampuan Pemecahan Masalah Matematika Menggunakan Model Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) Pada Siswa - Octafi, Febby Cipetra; Isnaniah, Isnaniah (Kadikma, 2022)
The purpose of this study was to determine whether the ability to solve mathematical problems using the Team Assisted Individualization (TAI) type cooperative learning model is better than conventional learning in class VIII of MTs Negeri 12 Agam in the 2021/2022 academic year. This type of research is a pre-experimental research with the research design of The Static Group Comparison Design. The study used two classes, namely the experimental class which was given treatment using a Team Assisted Individualization (TAI) cooperative learning model and the control class using conventional learning. The population in this study is class VIII MTs Negeri 12 Agam. The research samples were students of class VIII A as the experimental class and class VIII B of the control class. The research instrument used a mathematical problem solving ability test in the form of a description test. Based on the results of data analysis, the student's mathematical problem solving ability test is calculated by using the t-test, it is obtained and because , meaning that and are accepted, while using Minitab software, and . Thus, it can be concluded that students' mathematical problem solving skills using the Team Assisted Individualization (TAI) type cooperative learning model are better than conventional learning in class VIII of MTs Negeri 12 Agam in the 2021/2022 academic year.Keyword : Mathematical Problem Solving, Team Assisted Individualization (TAI) Model.